Chemical precipitation of ZnO nanoparticles: antimicrobial activity and in vivo sub-acute nanotoxicological impact on the liver and kidney of swiss albino mice - P. SURESH KUMAR,; A. SAMSON NESARAJ, (International Journal of Pharma and Bio Sciences, 2017)
ZnO nanoparticles can be used in wide range of applications including bionano products, electronics, food additives, sun screens, biosensors, etc. However, the comprehensive toxicological impact posed by ZnO nanoparticles still remains clear. In this research work, we report the preparation and toxicological study of ZnO nanoparticles by simple chemical precipitation method in our laboratory. The prepared ZnO nanoparticles were characterized by using X-ray diffraction, SEM and EADX. The nanoparticles were subjected to antimicrobial assay by agar well diffusion method against both Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram negative bacteria (Escherichia coli and Klebsiella pneumoniae). ZnO nanoparticles have maintained considerably multidrug resistance against the clinical pathogens such as Staphylococcus aureus and Bacillus subtilis (Gram positive bacteria) and Klebsiella pneumoniae and Escherichia coli and (Gram negative bacteria).The antibacterial efficiency of the nanoparticle mainly dependent on the size of the particle along-with other characteristics. The study was further extended to assess the in vivo sub –acute oral toxic effect of ZnO nanoparticles in Swiss Albino Mice. The invivo histopathological studies revealed that the mice treated with 500 mg/kgbwt dosage showed moderate toxicity in the central vein of the hepatocytes after 14 days. In conclusion, ZnO nanoparticle was found to show good antibacterial activity but however it causes moderate toxicity in the organs liver and kidney of Swiss Albino Mice after extensive dosage levels.